2022
DOI: 10.3390/life12071040
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Induction and Direct Antifungal Activity of Some Monoterpenes against Rhizoctonia solani, the Causal of Root Rot in Common Bean

Abstract: This study was conducted to evaluate eco-friendly control agents (carvone, cuminaldehyde, and linalool) against Rhizoctonia solani, which causes root rot disease either by induction of defense response or direct antifungal activity. The induction of resistance was examined by detecting the transcription of defense genes and the effect of the tested control agents on the growth and the yield of common bean plants. The growth of R. solani was significantly inhibited after treatment with the tested compounds comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Meanwhile, Tralamazza et al [15] have reported that this species complex is associated with panicle infection in wild rice in Brazil. Numerous research studies have explored the effectiveness of different extracts against R. solani, revealing encouraging outcomes regarding their antifungal properties [16][17][18]. Antifungal properties towards the fungi Aspergillus flavus, Candida spp., and A. niger were detected using water, alcohol, ether, and chloroform-derived extracts of S. macrophylla leaves [19].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Tralamazza et al [15] have reported that this species complex is associated with panicle infection in wild rice in Brazil. Numerous research studies have explored the effectiveness of different extracts against R. solani, revealing encouraging outcomes regarding their antifungal properties [16][17][18]. Antifungal properties towards the fungi Aspergillus flavus, Candida spp., and A. niger were detected using water, alcohol, ether, and chloroform-derived extracts of S. macrophylla leaves [19].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the untreated control, the use of fungicide alone or in combination with the RSB induced a slight, but not signi cant, reduction in the activity of PAL. When testing the effects of monoterpenes and the fungicide based on toclophos-methyl + thiram on common bean, Derbalah et al (2022) reported no signi cant differences in the expression of PAL when the fungicide was applied to plants (compared to the untreated control). On the other hand, the use of monoterpenes increased the expression of this enzyme, similar to the results observed with the use of the RSB on wheat plants.…”
Section: As Seen Inmentioning
confidence: 99%
“…The fungus was identified and maintained on PDA medium, with stock cultures being subcultured at intervals of 20-25 days [10]. Pathogen was morphologically identified with micro and macroscopically observed using compound microscope [11].…”
Section: Isolation and Morphological Identification Of Rhizoctonia So...mentioning
confidence: 99%
“…Spedaletti et al [7] identified R. solani based on the morphological characteristics viz., mycelium color, sclerotia formation, and nuclei count per hyphal cell. Derbalah et al [11] isolated R. solani from naturally infected common bean plants displaying symptoms of root rot and it was identified based on its morphological and microscopic characteristics. Heflish et al [17] isolated Rhizactonia solani from bean plants exhibiting characteristic symptoms on potato dextrose agar (PDA) plates and further purification of the pathogen was obtained by following hyphal tip technique.…”
Section: Morphological Identification Rhizoctonia Solani Kuhnmentioning
confidence: 99%